The Effect of Merger and Acquisition Announcements on Stock Price Behaviour and Financial Performance Changes: A Case of Banks in Malaysia - D. Agus Harjito; Zunaidah Sulong (Universitas Islam Indonesia, 2006)
This study attempts to examine the effect of mergers and acquisitions completion announcements on the stock price behavior for two anchor banks; Hong Leong Bank Berhad and Arab Malaysian Bank Berhad. The analysis uses the event study technique, the Naïve Model, a model that is based on Market Model with constrained  = 0 and  = 1 to compute the abnormal returns surrounding the mergers and acquisitions completion announcement date; also to evaluate the effect of mergers and acquisitions completion announcement on the banks’ return. This study also analyses the financial performance changes to provide a naïve analytical framework by using financial ratios for these two anchor banks. Overall, the result from event study shows that the mergers and acquisitions completion announcements are more likely to be treated as positive information. However, the results from financial performance measures for all the ratios, that are calculated, indicate that there is no improvement in any of the performance measures after the mergers and acquisitions is completed.Keywords: merger, acquisition, stock prices, financial performance.